Variable-structure repetitive control for discrete-time linear systems with multiple-period exogenous signals - Kurniawan, Edi; Harno, Hendra G.; Wijonarko, Sensus; Widiyatmoko, Bambang; Bayuwati, Dwi; Purwowibowo, Purwowibowo; Maftukhah, Tatik (Zielona Góra: Uniwersytet Zielonogórski)
A new method to construct a discrete-time variable-structure repetitive controller for a class of linear systems perturbed by multiple-period exogenous signals is presented. The proposed control scheme combines the features of the discrete-time multiple-period repetitive control (MP-RC) and variable-structure control (VSC) techniques. The MP-RC part is assigned to simultaneously track and reject periodic signals consisting of multiple uncorrelated fundamental frequencies.
Keywords: repetitive control; variable-structure control; multiple-period signals; fast transient response; robustness